2000
DOI: 10.1074/jbc.275.9.6167
|View full text |Cite
|
Sign up to set email alerts
|

HeLa Cells Are Phenotypically Limiting in Cyclin E/CDK2 for Efficient Human Papillomavirus DNA Replication

Abstract: Human papillomaviral (HPV) origin-containing plasmids replicate efficiently in human 293 cells or cell extracts in the presence of HPV origin-recognition protein E2 and replication initiation protein E1, whereas cervical carcinoma-derived, HPV-18-positive HeLa cells or cell extracts support HPV DNA replication poorly. We recently showed that HPV-11 E1 interacts with cyclin/ cyclin-dependent kinase (cdk) complexes through an RXL motif and is a substrate for these kinases. E1 mutations in this motif or in candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
37
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 59 publications
1
37
0
Order By: Relevance
“…HPV-11 E2 protein is a substrate of cyclin E-, A-, or B-dependent kinases (CDKs) in vitro in a complex which also contains the HPV-11 E1 protein (41). However, only cyclin E/cdk2 plays a unique role in initiation of replication that cannot be fulfilled by other CDKs (38). We note that several candidate CDK phosphorylation sites are located in the hinge region.…”
Section: Discussionmentioning
confidence: 99%
“…HPV-11 E2 protein is a substrate of cyclin E-, A-, or B-dependent kinases (CDKs) in vitro in a complex which also contains the HPV-11 E1 protein (41). However, only cyclin E/cdk2 plays a unique role in initiation of replication that cannot be fulfilled by other CDKs (38). We note that several candidate CDK phosphorylation sites are located in the hinge region.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the papillomavirus-encoded DNA helicase E1 and the primary origin recognition protein E2 are substrates of various cdks in vitro (9,24). In particular, phosphorylation of E1 by cyclin E/cdk2 is critical for efficient initiation of HPV DNA replication (23).…”
mentioning
confidence: 99%
“…However, a previous study using W12 cells, which were isolated from cervical intraepithelial lesion and retain HPV16 genomes as episomes (Stanley et al 1989), reported that replication of the HPV16 genome switches from a bidirectional to a unidirectional mode on cell differentiation, which implies a rolling circle mode of HPV replication (Flores & Lambert 1997). As an extract from HeLa cells was examined for its ability to support HPV replication without success (Lin et al 2000), in vitro HPV replication has not been studied using extracts from human epithelial cells.Here, to examine how HPV replication progresses in epithelial cells, we have employed an in vitro replication assay using crude extracts from differentiated epithelial cells. In addition to bidirectional replication, we have demonstrated that an extract from W12 cells induces a substantial level of rolling circle replication of an HPV16 origin-containing plasmid in a manner that depends on the presence of E1 and E2.…”
mentioning
confidence: 99%
“…However, a previous study using W12 cells, which were isolated from cervical intraepithelial lesion and retain HPV16 genomes as episomes (Stanley et al 1989), reported that replication of the HPV16 genome switches from a bidirectional to a unidirectional mode on cell differentiation, which implies a rolling circle mode of HPV replication (Flores & Lambert 1997). As an extract from HeLa cells was examined for its ability to support HPV replication without success (Lin et al 2000), in vitro HPV replication has not been studied using extracts from human epithelial cells.…”
mentioning
confidence: 99%